How a Training Program Is Transforming the Role of Traditional Birth Attendants from Cultural Practitioners to Unique Health-care Providers: A Community Case Study in Rural Guatemala - Hernandez, Sasha; Oliveira, Jessica Bastos; Shirazian, Taraneh (Frontiers in Public Health, 2017)
In low- and middle-income countries (LMICs), where the rates of maternal mortality continue to be inappropriately high, there has been recognition of the importance of training traditional birth attendants (TBAs) to help improve outcomes during pregnancy and childbirth. In Guatemala, there is no national comprehensive training program in place despite the fact that the majority of women rely on TBAs during pregnancy and childbirth. This community case study presents a unique education program led by TBAs for TBAs in rural Guatemala. Discussion of this training program focuses on programming implementation, curriculum development, sustainable methodology, and how an educational partnership with the current national health-care system can increase access to health care for women in LMICs. Recent modifications to this training model are also discussed including how a change in the clinical curriculum is further integrating TBAs into the national health infrastructure. The training program has demonstrated that Guatemalan TBAs are able to improve their basic obstetrical knowledge, are capable of identifying and referring early complications of pregnancy and labor, and can deliver basic prenatal care that would otherwise not be provided. This training model is helping transform the role of the TBA from a sole cultural practitioner to a validated health-care provider within the health-care infrastructure of Guatemala and has the potential to do the same in other LMICs.